Ugly freedoms - Anker, Elisabeth R. (Duke University Press, 2022)
"Elisabeth R. Anker reckons with the complex legacy of freedom offered by liberal American democracy, identifying modes of "ugly freedom" that can lead to domination or provide a source of emancipatory potential."--